The influence of social network on COVID-19 vaccine hesitancy among healthcare workers: a cross-sectional survey in Chongqing, China - Binyue Xu; Yi Zhang; Lei Chen; Linling Yu; Lanxin Li; Qing Wang (Taylor & Francis Group, 2021)
The factors that lead to coronavirus disease 2019 (COVID-19) vaccine hesitancy among health-care workers (HCWs) are unclear. We aimed to identify the factors that influence HCWs' hesitancy, especially the influence of their social network. Using an online platform, we surveyed HCWs in Chongqing, China, in January 2021 to understand the factors that influence the COVID-19 vaccine hesitancy among HCWs. Proportional allocation stratified sampling method was used to recruit respondents. Multivariable logistic regression and social network analysis (SNA) were used to analyze the influence factors. A total of 5247 HCWs were included and 23.3% of them were vaccine-hesitant. Participants were more hesitant if they had chronic diseases (OR = 1.411, 95% CI: 1.146-1.738), worked in tertiary hospitals (OR = 1.546, 95% CI: 1.231-1.942), and reported a history of vaccine hesitancy (OR = 1.637, 95% CI: 1.395-1.920) and refusal toward other vaccines (OR = 2.433, 95% CI: 2.067-2.863). The participants with a social network to communicate COVID-19 immunization were less hesitant (OR = 0.850, 95% CI: 0.728-0.993). Several influential members with social networks were found in SNA. Most of these influential members in the networks were department leaders who were willing to get COVID-19 vaccines (P < .05). Hesitant subgroups among Chinese HCWs were linked to the lack of a social network to communicate COVID-19 immunization. Our findings may lead to tailored interventions to enhance COVID-19 vaccine uptake among HCWs by targeting key members in social network.